Neuroception of psychological safety scale (NPSS): validation with a UK based adult community sample - Nicola Cogan; Liza Morton; John Campbell; Linda Irvine Fitzpatrick; Danielle Lamb; Johannes De Kock; Alisha Ali; David Young; Stephen Porges (European Journal of Psychotraumatology)
Background: Psychological safety plays a vital role in rest, recovery, and fostering social connections. However, a history of trauma can predispose individuals to perceive heightened levels of threat and danger. Research suggests that a lack of psychological safety may be a defining biopsychosocial characteristic of posttraumatic stress disorder (PTSD). Persistent feelings of threat and danger are associated with a lack of psychological safety and may be predictive of PTSD. Our pioneering work reported on the development of the neuroception of psychological safety (NPSS), rooted in polyvagal theory, and consists of social engagement, compassion, and body sensations dimensions. Understanding more about the dimensionality of the NPSS and further establishing its psychometric properties was our priority.Objective: Our current research aimed to validate and test the reliability and dimensionality of the NPSS, using a large community sample (n = 2035) of adult residents in the UKMethod: We examined the internal and test-retest reliability, convergent, discriminant, and concurrent validity as well as dimensionality of the NPSS.Results: The 3-factor structure of the NPSS was replicated with regard to the absolute fit indices. Internal consistencies ranged from acceptable to excellent across the NPSS’s subscales. Providing support for the validity of the NPSS, scores were predictably related to team psychological safety, wellbeing, post-traumatic stress, burnout, body awareness, and personality, with effect sizes typically in the high to medium range. Scores on the NPSS were found to show good test-retest reliability.Conclusions: This study demonstrates the validity, reliability and dimensionality of the NPSS with an adult sample. Further work is underway to support and enhance understandings of psychological safety with diverse clinical populations impacted by trauma. The NPSS has applicability across a range of health and social care contexts, such as shaping new approaches to evaluating trauma treatments and enhancing trauma informed care.